Gambaran Tingkat Pengetahuan dan Sikap Remaja terhadap Pencegahan Kekerasan Seksual di SMA Negeri 1 Surakarta - Erna Putri Lestari; Mulyaningsih Mulyaningsih (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Data from the National Commission on Violence Against Women (Komnas Perempuan) shows that between May 2022 and December 2023, there were 4,179 cases of sexual violence, including 2,776 cases of Electronic-Based Sexual Violence (KSBE) and 623 cases of rape. Adolescents' knowledge and attitudes play a crucial role in preventing sexual violence in schools. Objective: To determine the level of adolescents' knowledge and attitudes regarding sexual violence prevention at State Senior High School 1 Surakarta. Methods: A quantitative descriptive study with a cross-sectional approach involving 89 students in grades X and XI was conducted on January 20, 2026. Results: The results showed that most respondents had good knowledge (65 respondents, 73.0%), and 3 respondents (3.4%) had poor knowledge. The results also showed that most respondents had good attitudes (44 respondents, 49.4%) and 9 respondents (10.1%) had poor attitudes. Conclusion: Most Students had good  knowledge and attitudes regarding sexual violence prevention at SMA Negeri 1 Surakarta.